Upaya Meningkatkan Hasil Belajar Peserta Didik pada Mata Pelajaran Matematika Materi Penjumlahan Menggunakan Model Pembelajaran PBL (Problem Based Learning) Berbantuan Media Audio Visual Disertai Media Corong Penjumlahan di Kelas 1 SD Negeri 4 Kuningan (Fakultas Keguruan dan Ilmu Pendidikan Universitas Kuningan, 2023)
Abstract Learning mathematics is sometimes a problem for most students, because they consider learning mathematics to be difficult and boring, especially in addition material, which makes it difficult for students to carry out various forms of addition. With this assumption, it results in a lack of student motivation in studying mathematics, addition material, thus affecting students' low learning outcomes. This is the background to the problem of the research that the researcher conducted. Therefore, one learning model that can be used by researchers to overcome the low ability of class 1 students in understanding addition material is the PBL (Problem Based Learning) model assisted by Audio-Visual media accompanied by addition funnel media. This research is classroom action research. The subjects in this research were 18 grade 1 students at SD Negeri 4 Kuningan. The aim of this research is to determine the improvement in learning outcomes of grade 1 students in mathematics lessons on addition material. This research is collaborative between the principal, researchers and colleagues as observers. The instruments used to collect data are observation sheets, interviews, student response questionnaires and evaluation sheets, then the results of the analysis are presented using the Descriptive Statistical Analysis method. The results of this research show that in cycle 1 the learning outcomes of students were (66.67%) from 18 people with an average score of 77.78 and in cycle 2 they were (88.89%) from 18 people with an average score of 87. .78. Even though there are 2 people who still haven't achieved a complete/pass mark, based on the percentage of completeness they can be said to have succeeded well. From the analysis of the research data, it can be concluded that the application of the PBL (Problem Based Learning) learning model assisted by Audio-Visual media accompanied by addition funnel media can improve student learning outcomes in the addition material in class 1 Mathematics lessons at SD Negeri 4 Kuningan. Keywords: PBL model, Audio-Visual Media, Addition funnel media, Summation, Learning outcomes